A banda vai passar: oficinas de banda fanfarra no Programa Mais Educação em escolas de Cabedelo - Félix, Michel Charles Nunes (2013)
The work presents a discussion about the conception of full-time education throughout the centuries and from its start in Brazil and the role of the expansion of the school day in this education perspective, presenting the Programa Mais Educação and its conception about fulltime education. This dissertation is a result of a multiple case study, when we studied pedagogical musical practices developed in fanfare band workshops offered by the Programa Mais Educação in two state schools located in Cabedelo. The Mais Educação is a program developed by the federal government that aims to foment the full-time education in Brazil, offering difference educational activities divided in ten macro-ﬁelds, for example, the fanfare band. The work emphasises the musical bands as a way to musical learning in Brazil and its function throughout the centuries, besides the repeated teaching and learning music processes that are characteristic of this space of musical formation. On the Programa Mais Educação, the fanfare band is part of the macro-ﬁeld Culture and Art. Thus, we adopted, as our general objective for this research, knowing and analysing how the teaching and learning process is characterized in each fanfare workshop researched. As speciﬁc objectives we aim to discuss the conceptions of full-time education and education in integrated time, based on different authors; to verify the pedagogical practice developed in the music workshop; to characterise the educators who work on these contexts and their formation. The methodology consisted of a bibliography research in the pedagogy and music education ﬁeld and also of a documental research, in which documents related to the Programa Mais Educação were analysed. In the ﬁeld research, the data collecting instruments were: observation of the pedagogic practices developed in two workshops, besides the semi-structured interviews with the state coordinator of Mais Educação and its directors, teachers and monitors of each school. The analyse was made though the interchange of the data collected in the observations and interviews with the theoretical referential and the documental data. The two cases investigated point to the singularity of how each fanfare band is constituted as a educative space, each one with characteristics that depend on many factors, like the monitor’s experience, the way each school applies the program and the facilities and resources available. The schools investigated, in relation to the selection of students and monitors, follow criteria different from the ones proposed by the Mais Educação manual, what reﬂects the decentralisation, which is a characteristic of the program. However, the results of the fanfare band workshops of both schools are shown in a public parade, as the September seventh, pointing out that though the pedagogic processes of each teacher, though different, lead to signiﬁcative musical results.